2020
DOI: 10.3389/fphar.2020.578887
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Adherence-Enhancing Interventions for Immunosuppressive Therapy in Solid Organ Transplant Recipients: A Systematic Review and Meta-Analysis Based on Randomized Controlled Trials

Abstract: Background: Immunosuppressant non-adherence is a widespread problem among solid organ recipients. With the newly published clinical trials, the randomized controlled trials (RCTs) based systematic review of adherence-enhancing interventions on immunosuppressant adherence in solid organ recipients has not been completed. In this systematic review and meta-analysis, we compared the efficacy of adherenceenhancing interventions versus routine intervention, as performed with RCTs, on immunosuppressant adherence in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
0
15
0
1
Order By: Relevance
“…A meta-analysis by Shi et al in October 2020 reviewed 27 articles regarding adherence-enhancing interventions in solid organ transplant recipients. The authors reported a promising correlation between the use of interventions and higher patients' selfreported adherence, but interestingly not with immunosuppressant drug levels, suggesting further research is necessary [33].…”
Section: Innovation In Digital Approachesmentioning
confidence: 96%
“…A meta-analysis by Shi et al in October 2020 reviewed 27 articles regarding adherence-enhancing interventions in solid organ transplant recipients. The authors reported a promising correlation between the use of interventions and higher patients' selfreported adherence, but interestingly not with immunosuppressant drug levels, suggesting further research is necessary [33].…”
Section: Innovation In Digital Approachesmentioning
confidence: 96%
“…Therefore, a repeat TDM at an accurate sampling time might be necessary. Moreover, educating patients and their family caregivers about sampling adherence is crucial (Shi et al, 2020). Medical workers also require education about pharmacokinetics and TDM, and laboratory technicians and nurses should be reminded about correct sampling times and their importance (Schiff et al, 2003;Chen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Patient adherence remains a major barrier in achieving long-term survival following solid organ transplantation, including the lung ( 227 229 ). A recent meta-analysis evaluating the efficacy of interventions aimed at improving adherence identified the importance of a multidisciplinary team, a comprehensive intervention approach, and mobile health monitoring ( 230 ). Indeed, optimization of strategies that increase patient adherence represents an important aspect for improved outcomes following lung transplantation.…”
Section: Tolerance Inductionmentioning
confidence: 99%